Using Boops boops (osteichthyes) to assess microplastic ingestion in the Mediterranean Sea. (September 2020) - Tsangaris, Catherine; Digka, Nikoletta; Valente, Tommaso; Aguilar, Alex; Borrell, Asunción; de Lucia, Giuseppe Andrea; Gambaiani, Delphine; Garcia-Garin, Odei; Kaberi, Helen; Martin, Jessica; Mauriño, Elena; Miaud, Claude; et al.
Abstract: This study assesses microplastic ingestion in Boops boops at different geographical areas in the Mediterranean Sea. A total of 884 fish were caught at 20 coastal sites in Spain, France, Italy and Greece and analyzed using a common methodological protocol. Microplastics were found in 46.8% of the sampled fish, with an average number of items per individual of 1.17 ± 0.07. Filaments were the predominant shape type, while polyethylene and polypropylene were indicated by FTIR as the most common polymer types of ingested microplastics. The frequency of occurrence, as well as the abundance and proportion of types (size, shape, color and polymer) of ingested microplastics, varied among geographical areas. The spatial heterogeneity of the abundance of ingested microplastics was mainly related to the degree of coastal anthropogenic pressure at the sampling sites. Our findings further support the suitability of B. boops as bioindicator of microplastic pollution in the Mediterranean Sea. Highlights: High incidence of microplastic ingestion in Boops boops from the Mediterranean Sea Ingested microplastics were predominantly filaments. Polyethylene and polypropylene were the most common polymers detected. Frequency of occurrence, abundance and types of microplastics varied spatially. Microplastic abundance related to coastal anthropogenic pressure